2018
DOI: 10.1093/ije/dyy253
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing with soap after potential faecal contact: global, regional and country estimates

Abstract: Background Limited data have been available on the global practice of handwashing with soap (HWWS). To better appreciate global HWWS frequency, which plays a role in disease transmission, our objectives were to: (i) quantify the presence of designated handwashing facilities; (ii) assess the association between handwashing facility presence and observed HWWS; and (iii) derive country, regional and global HWWS estimates after potential faecal contact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 33 publications
5
79
0
2
Order By: Relevance
“…We found that more than three-quarters of the survey participants have taken some preventive actions, including social distancing, handwashing, coughing etiquette, and strengthening immunity. Because the previous empirical studies did not include developed countries like Japan, [17] there is little scientific evidence that Japanese people prefer cleanliness and tend to wash their hands relatively more frequently than other countries. In Japanese communities, water facilities for handwashing with soap and hand sanitizers are normally placed various public places, such as train stations and supermarkets.…”
Section: Discussionmentioning
confidence: 99%
“…We found that more than three-quarters of the survey participants have taken some preventive actions, including social distancing, handwashing, coughing etiquette, and strengthening immunity. Because the previous empirical studies did not include developed countries like Japan, [17] there is little scientific evidence that Japanese people prefer cleanliness and tend to wash their hands relatively more frequently than other countries. In Japanese communities, water facilities for handwashing with soap and hand sanitizers are normally placed various public places, such as train stations and supermarkets.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that the presence of soap and water on premises may not necessarily reflect handwashing practices at critical times such as before and after meal preparation, eating and after visiting the toilet. Biran et al in 2008 made the valid point that estimating handwashing through observation of facilities with soap may be poorly associated with actual handwashing practices [47] and even among those with access, handwashing is often inadequately practiced [48].…”
Section: Plos Onementioning
confidence: 99%
“…Other studies of handwashing behaviour in refugee camps receiving regular soap distributions in Ethiopia found HWWS rates of 4% (15) and 19% (13). A recent review of national survey data estimated that rates of HWWS after toilet use are likely to be about 8% within the World Health Organisation African region (32). It is possible that it was the distribution of the handwashing facility itself, rather than soap or mirrors, that made a more substantial contribution to encourage handwashing behaviour (both with water only and with soap) but this study was not designed to measure this.…”
Section: Discussionmentioning
confidence: 99%